Superior Mesenteric Artery Syndrome: An Infrequent Complication of Scoliosis Surgery - Metin Keskin; Turgut Akgül; Adem Bayraktar; Fatih Dikici; Emre Balık (Case Reports in Surgery, 2014)
Superior mesenteric artery syndrome is a rare condition that causes a proximal small intestinal obstruction due to contraction of the angle between the superior mesenteric artery and the aorta. Scoliosis surgery is one of the 15 reasons for superior mesenteric artery syndrome, which can present with acute or chronic manifestations. Although conservative treatment is usually possible, surgical treatment is required in certain cases that cannot be treated using conservative methods. In this paper, we describe a patient who developed superior mesenteric artery syndrome after scoliosis surgery and was treated with duodenojejunostomy due to failure and complications of conservative treatment.